Implication of condemnatoir verdict in the case of child custody rights in the legal way of The Denpasar Agency (Case study of case No. 358/PDT. G/2023/PA. DPS) - Sarasanjaya, I Komang Gemini; Wiratny, Ketut; Nurindahwati, Zuhro (International Journal Labs, 2024)
This study aims to find out the implications of condemnatoir decisions in child custody cases in the jurisdiction of the Denpasar Religious Court, and the obstacles faced in the implementation of the execution of child custody decisions in this jurisdiction. The study employs both normative and empirical approaches, focusing on the norm vacuum regarding the enforcement of Hadhanah (child custody) decisions. The data analysis involves a legal analysis of the normative sources to interpret and evaluate the current laws, complemented by qualitative analysis of empirical data to identify patterns, issues, and challenges in the execution process. The research offers valuable insights into the practical difficulties of enforcing child custody rulings, which could inform legal reforms or improvements in the judicial process to better protect the interests of the child and ensure compliance with judicial decisions.